Holy or wholly? : a systematic theological study of Sabbath keeping in the works of Samuele Bacchiocchi and Marva J. Dawn - Mats’aba, Kofo (Stellenbosch : Stellenbosch University, 2018)
Thesis (MTh)--Stellenbosch University, 2018.